Enhanced Ultraviolet Spectroscopy by Optical Clearing for Biomedical Applications - Carneiro, Isa (2021)
In this paper, we describe the combination of ultraviolet (UV) spectroscopy with the optical clearing technique to induce new tissue windows, evaluate their efficiency, study the diffusion properties of agents and discriminate cancer. The use of highly concentrated glycerol solutions has induced high efficiency clearing effects in the UV, both in human colorectal and gingival tissues. The protein dissociation rate obtained for colorectal tissues was approximately 3 times higher in pathological than in normal mucosa and the kinetics of diffuse reflectance in the UV allowed to estimate the diffusion coefficient for water in gingival mucosa at glycerol action as (1.78 ± 0.26) × 10 -6 cm 2 /s.